Narcissistic Narrative : The Metafictional Paradox - Hutcheon, Linda, 1947- (Book collections on Project MUSE., 2013)
Linda Hutcheon, in this original study, examines the modes, forms and techniques of narcissistic fiction, that is, fiction which includes within itself some sort of commentary on its own narrative and/or linguistic nature. Her analysis is further extended to discuss the implications of such a development for both the theory of the novel and reading theory. Having placed this phenomenon in its historical context Linda Hutcheon uses the insights of various reader-response theories to explore the "paradox" created by metafiction: the reader is, at the same time, co-creator of the sel.